2020
DOI: 10.18632/aging.103653
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG12 promotes immune escape of ovarian cancer cells through their crosstalk with M2 macrophages

Abstract: Accumulating evidence shows that the tumor microenvironment contributes to this phenomenon and that long non-coding RNAs (lncRNAs) are also involved in this process. In this study, we identified a new lncRNA small nucleolar RNA host gene 12 (SNHG12) and investigated its role in tumor immune escape. We analyzed the expression levels of interlukin (IL)-6R and programmed death-ligand 1 (PD-L1) in 51 ovarian cancer and 20 normal specimens by immunohistochemistry. The correlation between SNHG12 and IL-6R in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…Classically, in response to microenvironmental stimuli, TAMs polarize to M1like phenotype exhibiting proinflammatory and tumor-inhibiting phenotypic effects, while certain cytokines convert TAMs into an M2-like phenotype with anti-inflammatory but tumor-promoting functions (38,39). Previous studies have shown that M2 macrophages elevated PD-L1 expression in cancer cells and at the same time facilitating immune escape (40,41). As for M1 macrophages, the PD-L1 expressed on the surface was also reported to result in immune escape of cancer cells, resulting in bidirectional effects of both anti-tumoral and pro-tumoral activities (42): On one hand, M1-like phenotype had the unique ability to promote the activation and recruitment of various immune effectors, performing surveillance tasks (43), and their infiltration indicated good prognosis in some cancers (44).…”
Section: Pd-l1 Overexpression Has Been Demonstrated In Many Common Cancers Inducing T-cell Tolerance and Promoting Immune Escapementioning
confidence: 99%
“…Classically, in response to microenvironmental stimuli, TAMs polarize to M1like phenotype exhibiting proinflammatory and tumor-inhibiting phenotypic effects, while certain cytokines convert TAMs into an M2-like phenotype with anti-inflammatory but tumor-promoting functions (38,39). Previous studies have shown that M2 macrophages elevated PD-L1 expression in cancer cells and at the same time facilitating immune escape (40,41). As for M1 macrophages, the PD-L1 expressed on the surface was also reported to result in immune escape of cancer cells, resulting in bidirectional effects of both anti-tumoral and pro-tumoral activities (42): On one hand, M1-like phenotype had the unique ability to promote the activation and recruitment of various immune effectors, performing surveillance tasks (43), and their infiltration indicated good prognosis in some cancers (44).…”
Section: Pd-l1 Overexpression Has Been Demonstrated In Many Common Cancers Inducing T-cell Tolerance and Promoting Immune Escapementioning
confidence: 99%
“…Two lncRNAs AC104699.1.1 and RP11-284 N8.3.1 have been reported to exert protective effects throughout the progression of ovarian carcinoma and were related to the antitumor processes and activation of the immune system in the microenvironment [ 17 ]. A recent study showed that lncRNA SNHG12 facilitates immune escape of ovarian carcinoma cells by their crosstalk with M2 macrophages [ 18 ]. Therefore, it is reasonable to suggest that immune-associated lncRNAs may be the potential biomarkers for ovarian carcinoma patients and may serve as possible therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…SNHG12 exerts a carcinogenic effect in a variety of cancers [12][13][14][15][16][17][18][19][20][30][31][32]. In clear cell RCC, SNHG12, as a competitive endogenous RNA, competes with miR-30a-5p to bind downstream oncogenes RUNX2, IGF-1R and WNT2 to promote tumor cell invasiveness [33].…”
Section: Discussionmentioning
confidence: 99%